Relevance of polyp size for primary endoscopic full-thickness resection of suspected T1 colorectal cancers - Didden, Paul; van Eijck van Heslinga, Rixta A. H.; Schwartz, Matthijs P.; Arensman, L. R.; Vleggaar, Frank P.; de Graaf, Wilmar; Koch, Arjun D.; Doukas, Michael; Lacle, Miangela M.; Moons, Leon M. G. (Endoscopy, 2022)
Background En bloc local excision of suspected T1 colorectal cancer (CRC) provides optimal tumor risk assessment with curative intent. Endoscopic full-thickness resection (eFTR) with an over-the-scope device has emerged as a local excision technique for T1 CRCs, but data on the upper size limit for achieving a histological complete (R0) resection are lacking. We aimed to determine the influence of polyp size on the R0 rate.Methods eFTR procedures for suspected T1 CRCs performed between 2015 and 2021 were selected from the endoscopy databases of three tertiary centers. The main outcome was R0 resection, defined as tumor- and dysplasia-free margins (≥ 0.1 mm) for both the deep and lateral resection margins. Regression analysis was performed to identify risk factors for R1/Rx resection, mainly focusing on endoscopically estimated polyp size.Results 136 patients underwent eFTR for suspected T1 CRC (median size 15 mm [IQR 13–18 mm]; 83.1 % cancer). The rates of technical success and R0 resection were 87.5 % (119/136; 95 %CI 80.9 %–92.1 %) and 79.7 % (106/136; 95 %CI 72.1 %–85.7 %), respectively. Increasing polyp size was significantly associated with R1/Rx resection (risk ratio 2.35 per 5-mm increase, 95 %CI 1.80–3.07; P < 0.001). The R0 rate was 89.9 % (80/89) for polyps ≤ 15 mm, 71.4 % (25/35) for 16–20 mm, and 11.1 % (1/9) for those > 20 mm.Conclusions eFTR is associated with a 90 % R0 rate for T1 CRCs of ≤ 15 mm. Performing eFTR for polyps 16–20 mm should depend on access, their mobility, and the availability of alternative resection techniques. eFTR for > 20-mm polyps results in a high R1 rate and should not be recommended.